COVID-19 pandemic and total mortality in the first six months of 2020 in Italy: COVID-19 pandemic and total mortality - Alicandro, Gianfranco; Remuzzi, Giuseppe; La Vecchia, Carlo (La Medicina del Lavoro, 2020)
Based on mortality data from 93% of Italian municipalities, there was an over 50% excess total mortality in March and a 38% excess in April, corresponding to over 46,000 excess deaths in those two months – as compared to 28,000 deaths attributed to COVID-19 in March and April. No subsequent excess mortality was observed, and in June reported total deaths were 6.2% less than expected. In the first 6 months of 2020, an 11.1% excess mortality was observed in Italy, and an almost 50% excess in Lombardy, the most affected region. Timely monitoring of total mortality has relevant implications for monitoring the COVID-19 pandemic and controlling occupational and social exposures.